Quantitative Measurement Of Wallrock Alteration In The Exploration Of Buried Mineral Deposits - D. M. Hausen (Society for Mining, Metallurgy & Exploration, 1978)
A quantitative x-ray diffraction method has been developed for the analysis of alteration minerals in wallrock. Alteration data are plotted and contoured (analogous to geochemical data). Alteration trends outlined by this technique correlate closely with geochemical anomalies, and in some cases attend well beyond the perimeter of anomalous base metal values. "Monomineralic contouring," applied originally to porphyry-type mineralization, has been extended to other types of mineralization, including volcanogenic massive sulfide deposits. Equipment and techniques used in the quantitative measurement of alteration mineralogy are discussed.